A Agroecologia como elemento pedagógico: uma análise de experiências em escolas de diferentes regiões do Brasil - Mendonça, Thamirys Ramos de (Universidade Federal de São Carlos, 2021)
Agroecology can be understood as a science and as a practice, connecting itself in different ways with other fields of knowledge. In recent decades, agroecology has been inserted in the educational context at different levels, from basic to higher, technical and technological education. In elementary school, which covers students from 1st to 9th grade, agroecology can be presented as a complementary and multidisciplinary activity, associated with the principles of environmental education, established by the National Environmental Education Policy (PNEA). Experiences in this sense have already been developed in Brazilian schools, aiming to present the concepts and practices of agroecology in a playful and educational way. In this article, we seek to present the results of a literature review that aimed to survey experiences of activities in agroecology in elementary education in Brazil, based on 5 case studies in schools from different regions. Among the practices worked on in schools, the relevance of the school garden as a research and teaching laboratory, as well as composting and seedling production was verified. It was found that, based on such practices, themes such as food safety, healthy habits, environmental preservation, ecology and society could be discussed with the students. It is concluded that, although there is no legal obligation to guide agroecology as a curricular component, this inclusion can bring pedagogical benefits to the school context, as it allows for the discussion of multidisciplinary themes, especially in urban schools, in which the environmental theme is agriculture is not daily present in the reality of the student community. In this sense, the importance of planning activities that is based on the reality of each school is highlighted, which can be done from a Rapid Participatory Diagnosis (DRP) and other participatory methodologies that allow the educator to have a better understanding. assertion of the reality of the student community.
Agroecology as a pedagogical element: an analysis of experiences in schools in different Brazilian regions
Keywords: Agroecologia; Educação ambiental; Educação formal; Escolas brasileiras; Práticas agroecológicas; Agroecological practices; Agroecology; Brazilian schools; Environmental education; Formal education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO